From athletic excellence to academic influence: a study of retired Chinese athletes transitioning into the higher education sector - Zhou, Yutao; Zhang, Zhiming (Frontiers in Psychology, 2024)
While the career transition of athletes has been explored to several extents, it is often marked by complex psychosocial challenges and requires a redefined sense of identity and professional purpose.Research to date has predominately focused on the disadvantages or inequity emerging from broad social demographics without delving into specific career transition pathways, such as into higher education settings. This study specifically investigates the unique psychosocial factors underlying the career transition of retired Chinese athletes into higher education. We conducted an interview phase with retired Chinese athletes (Phase 1, n = 17) and a Delphi phase with senior human resources (HR) managers from Chinese higher education settings (Phase 2, n = 15). This approach allowed us to understand the lived experiences and challenges of these athletes within the Chinese cultural and social context, as well as HR experts' perceptions of their career transitions, respectively. The results unveil crucial psychosocial factors that motivate, and the barriers that challenge, and difficulties retired Chinese athletes in their transition, informing intervention and policy efforts to facilitate their successful integration into higher education.